Pengaruh Bone Marrow Mesenchymal Stem Cells Terhadap Sekresi VEGF pada Penyembuhan Luka Bakar Tikus - Gusti Revilla (Jurnal Kesehatan Andalas, 2017)
Treatment for burns have been carried out in various ways, but have not provided satisfactory results, so that using stem cells is necessary. Administering Bone Marrow Mesenchymal Stem Cells (BM-MSCs) for healing, are by accelerating the formation of granulation tissue, however the effectiveness of the provision of is still under exploration. The objective of this study was to determine the effect of the administration of stem cells BM-MSCs on VEGF secretion on burn healing process in rats. This research was an experimental research with design the post-test only control, using 12 Wistar rats, divided into 2 groups: control (PBS), treatment (BM-MSCs), stem-cells subcutaneously administered dose of 2 x 106 cells / ml. Before that the treated rats anesthetized using xylazine and ketamine then burns are made on the dorsal with full thickness degrees. On day 3 and 7, blood were obtained to measure levels of VEGF was measured by ELISA. The results were analyzed by t-test. Levels of VEGF in day 3 and day 7 in the group given BM-MSC were dereased 12.875 pg/ml dan 23.917 pg/ml compared to the control group 61.667 pg/ml and 200.042 pg/ml and showed significant differences p= 0.012 and p=0.038. The conclusion of this study is the administration of BM-MSCs were the influence levels of VEGF which has into differentiate to cells that contribute to angiogenesis was can to granulation tissue.